Teacher–Parent Collaboration in Fostering Islamic Character Development among Junior High School Students - Stepi Andini Putri; Rina Juliana (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This study examines the collaboration between Islamic Religious Education (PAI) teachers and parents in fostering students' Islamic character at SMP Negeri 17 Tanjung Jabung Timur, a topic of growing importance amid the moral challenges facing Indonesian adolescents in the digital era. The purpose of this research is to describe the forms of collaboration between PAI teachers and parents, and to identify the supporting and inhibiting factors involved. This topic is significant because character formation cannot rely solely on school-based instruction but requires consistent reinforcement at home. This study employed a qualitative descriptive approach, with data collected through observation, semi-structured interviews, and documentation, involving PAI teachers, students, parents, and the school principal as informants. The findings reveal that collaboration is implemented through structured religious habituation programs at school, the use of the "7 Habits of Outstanding Indonesian Children" journal as a monitoring instrument, and a continuous role-sharing system between teachers and parents. The most critical inhibiting factor is the lack of parental control over students' nighttime gadget use, which directly undermines the religious discipline built at school. This study contributes a practical model of continuous supervisory role-sharing that can serve as a reference for Islamic character education policy in public schools.